The rise of chatbots: The effect of using chatbot agents on consumers' responses to request rejection - Yu, Shubin; Xiong, Ji (Jill); Shen, Hao (Journal of Consumer Psychology, 2024)
AbstractThis research investigates consumers’ perceptions and evaluations of robot service agents compared with human service agents when service requests are rejected. Six studies were conducted. The results show that when consumers receive a rejection of their service request, they evaluate the service less negatively if the service is handled by a chatbot agent versus a human agent. The reason is that consumers have lower expectations that robots will be able to provide flexible services to them. Consequently, their dissatisfaction with the request rejection is lower when the service is handled by robots. However, the aforementioned effect is not observed (1) when consumers have not experienced the service yet, (2) when their service request has been accepted, or (3) when the service agent conveys emotions to apologize for request rejection.